'Composition of Place' and 'Application of the Senses' in Ignatian Prayer. Issue 2 (April 2019) - Almeida, Juliano Ribeiro
This article intends to investigate two moments proposed by Ignatius of Loyola during the experience of the Spiritual Exercises: Composition of place and Application of the senses. The proposal is to research the true goal and importance of these two practices during the times of prayer, in order to find out if they are necessary or dispensable in Ignatian style of meditation and contemplation. Are they for beginners or for experienced retreatants? Are they supposed to be exclusively a human initiative or does divine grace have a role in it too? How is it possible to distinguish if the person is been touched by God or only imagining?